Interaction of bacterial extracellular microvesicles with eukaryotic cells. - D. S. Shlykova; V. M. Pisarev; A. M. Gaponov; A. V. Tutelyan (Медицинская иммунология, 2021)
Bacterial extracellular microvesicles (BMV) are formed by nonpathogenic, pathogenic and opportunistic bacteria. BMV are spherical bilayer-membrane organelles containing different cargoes: lipopolysaccharides, pathogen associated molecular patterns (PUMP), DNA, RNA, signal molecules, proteins, antibiotic resistance factors, virulence factors, toxins providing various immune response options and conducive to the survival and pathogen dissemination in the human body. BMVs secretion play an important role in the ability of microorganisms to cause various diseases. BMV are involved in biofilms formation, help bacteria to obtain nutrition in a nutrient-poor conditions, to evade the host's immune response, provide communication and surviving in a stressful environment during infection inside the host. The heterogeneity of the biogenesis mechanisms causes differences in the BMV and their characteristics including virulence rate. BMVs host cells entering is mediated by several mechanisms and helps to activate innate and adaptive immune reactions. This review focuses on interaction study of BMV with various eukaryotic cells types including neutrophils, dendritic cells, macrophages, epithelial, endothelial cells. This interaction depends on bacteria species, type of target cell and number of vesicles and can lead to different responses: non-immunogenic, pro-inflammatory, cytotoxic. Subcellular and molecular mechanisms related to the involvement of extracellular microvesicles in host's immune response modulation are presented. Stimulation of immune response is provided by increased secretion of proinflammatory cytokines and chemokines. In some cases BMV use mechanisms to evade immune surveillance: anti-inflammatory cytokines secretion, alterations of phagocytosis and chemotaxis of macrophages, increasing the proteolytic cleavage of CD14 on the macrophage surface, alterations of antigen-presenting function of dendritic cells, T-cell proliferation suppression, reducing the pro-inflammatory cytokines secretion, evasion of host-immune cells direct interactions, destruction of neutrophilic traps. These features allow bacterial cells to survive in the human body, increase their invasive potential, and reduce the excessive inflammatory reactions leading to death of the pathogen itself and life-threatening damage of tissues and organs of the host. Further studies of these mechanisms will improve existing therapeutic approaches to the infectious diseases treatment.